APLIKASI SCORE CARD UNTUK PENILAIAN KINERJA PENGELOLAAN SUNGAI - Lutfiati, Anis (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
Evaluation activity should basically clear and provide context for the improvement ofmanagement processes for the better future . This should be realized by every management withinthe company wherever located . Clarity measurement tools will help achieve the objectives of thecompany later . One of the measuring instruments are applied is BSC (Balance Score Card ).BSC Assist management to evaluate and help correct the exact performance of the company.At first , the BSC is used to improve executive performance measurement system. Early use of theexecutive's performance is measured only in terms of finances. Then developed into a morespacious with four perspectives, which are then used to measure the performance of theorganization as a whole . The four perspectives, namely financial, customer, internal businessprocesses and learning and growth .In the development of the BSC has helped many companies to successfully achieve its goals. BSChas several advantages that are not owned traditional systems management strategy. Theadvantages of the BSC approach in the strategic planning system is able to produce a strategicplan, which has the characteristics : a comprehensive, coherent, balanced and measured .Basin , is an area that needs attention . Governments and communities must work together toachieve clean rivers, healthy, and productive and provide sustainable benefits to the surroundingcommunity. If the indicators are assessed in the score card is identical to the indicators used inthe monitoring and evaluation of the basin, the score card is also a tool for monitoring andevaluation of the river basin